Operational oceanography implementation at the European and regional scales : proceedings of the Second International Conference on EuroGOOS, 11-13 March 1999, Rome, Italy - Flemming, N. C. (Elsevier, 2002)
The Global Ocean Observing System (GOOS) is an international programme for a permanent global framework of observations, modelling and analysis of ocean variables that are needed to support operational services around the world. The EuroGOOS strategy has two streams: the first is to improve the quality of marine information in European home waters, and the second is to collaborate with similar organisations in other continents to create a new global ocean observing and modelling system that will provide the open ocean forecasts needed to achieve the best possible performance by local marine information services everywhere. EuroGOOS held its second international conference in The Hague in 1999. Here, the operational services already in place in the EuroGOOS regions were presented and evaluated. In addition, a "Forward Look" was presented, with targets for the next 5-10 years. The proceedings of the first EuroGOOS conference were published by Elsevier in the http://www.sciencedirect.com/science/publication?issn=04229894 & volume=66<HREF>/locate/inca/600827</HREF><HTXT>EOS Series No. 62</HTXT> Editors: Stel et al, ISBN 0-444-82892-3.
Keywords: Oceanography -- Remote sensing -- Congresses.; Oceanography -- Europe -- Congresses.; Europe.; elektronické knihy; electronic books